Corrosion behaviour of 2205 duplex stainless steel in pure cultures of sulphate reducing bacteria: SEM studies, electrochemical characterisation and biochemical analyses. Issue 1 (21st August 2017) - Dec, W.; Jaworska‐Kik, M.; Simka, W.; Michalska, J.
Abstract : The paper presents the results on biofilm formation induced by pure Desulfovibrio desulfuricans strains and its effect on corrosion behaviour of 2205 duplex stainless steel (DSS). Biofilm formation and damage process stimulated by D. desulfuricans strains are analysed with reference to their metabolic activity and to the surface characterisation of structure and configuration of the biofilm. Electrochemical techniques are applied to monitor bacterial attachment to the steel surface and to determine the influence of bacteria on the passivity and corrosion resistance of 2205 DSS. The obtained results prove that 2205 DSS is rapidly colonised by D. desulfuricans and that the biofilms formed affect its corrosion resistance. Bacterial activity leads to the more noble corrosion potential values and to the increased current densities on the potentiodynamic polarisation curves. SEM observations reveal micropits as well as signs of crevice attack on the steel surface. Abstract : The obtained results prove that 2205 DSS is intensively colonised by Desulfovibrio desulfuricans and that the biofilms formed affect its corrosion resistance and change the mechanism of corrosion. SRB led to the selective development of pitting within the ferrite (α) islands. Moreover, bacterial activity leads to more noble corrosion potential values and to increased current densities.